Investigating the influence of steel fibre on self-healing in stone mastic asphalt mixtures using the indirect tensile strength test: A case study aligned with the Sustainable Development Goal (SDG) 9 - Shaffie, Ekarizan; Shiong, Fionna; Azahari, Adib Zafri; Arshad, Ahmad Kamil; Hashim, Wardati; B. Ali, Ahmed Suliman; Putra Jaya, Ramadhansyah (Human Resource Management Academic Research Society, 2024)
This study driven by the urgent need to improve the durability and resilience of road infrastructure in response to increasing traffic loads and environmental challenges. By focusing on the self-healing properties of Stone Mastic Asphalt (SMA) mixtures, this study aims to tackle a critical challenge in pavement engineering; by focusing on the self-healing properties of Stone Mastic Asphalt (SMA) mixtures, this study aims to tackle a critical challenge in pavement engineering, thereby reducing the frequency and cost of road maintenance while ensuring sustainable road performance. SMA is a gap-graded hot mix commonly utilized for heavily trafficked roadways, providing 30% to 40% enhanced resistance to permanent deformation and rutting relative to dense-graded asphalt. SMA's higher binder content increases its susceptibility to moisture-induced degradation and variations in temperature, necessitating modifications to improve its durability. The incorporation of steel fibre has been identified as a viable solution, enhancing moisture resistance and self-healing capabilities. This study aimed to assess the effectiveness of incorporating steel fibre into SMA mixtures, with particular emphasis on enhancements in specific gravity, abrasion resistance, and indirect tensile strength. This study investigated four proportions of steel fibres (0%, 0.30%, 0.50%, and 0.70%) in SMA mixtures with a 6.2% PEN 60/70 binder content. Comprehensive testing, which included specific gravity, Marshall stability, and indirect tensile strength tests, was performed to evaluate performance. The findings indicated that the incorporation of steel fibre markedly improved the tensile deformation resistance, stability, and abrasion resistance of the SMA mixture. The 0.30% steel fibre proportion yielded the most favorable performance enhancement among the tested ratios. This research supports the SDG 9 objective of promoting resilient and sustainable infrastructure by demonstrating that steel fibre-modified asphalt mixtures improve the durability and safety of road structures.